Exploration of teaching practice of analgesia and sedation in mainland China: CASER experience - Su, Longxiang; Li, Shu; Lou, Ran; Liu, Ying; Zhang, Hua; Jiang, Li (Frontiers in Medicine, 2023)
Objective Analgesia and sedation assessments vary widely in clinical performance. This study investigated the cognition of intenvist and the importance of training for analgesia and sedation though the Chinese Analgesia and Sedation Education & Research (CASER) group training program. Methods A total of 107 participants studied the training courses on the "Sedation, Analgesia and Consciousness Assessment of Critically Ill Patients" held by CASER from June 2020 to June 2021. Ninety-eight valid questionnaires were recovered. The content of the questionnaire included the preface, general information of the trainees, students' awareness of the importance of analgesia and sedation evaluation and related guidelines, and professional test questions. Results All respondents were senior professionals engaged in the ICU. A total of 92.86% believed that analgesia and sedation treatment were very important parts of the ICU, and 76.5% believed that they had mastered relevant professional knowledge. However, when evaluating the relevant professional theory and practice of the respondents from an objective point of view, it can be seen that only 28.57% of the respondents could reach the passing line in the specific case analysis scenario. Before participating in the training, 42.86% of the medical staff believed that analgesia and sedation treatment should be evaluated in the daily work of the ICU; after participating in the training, 62.24% of the medical staff believed that the evaluation was necessary and believed that they had improved after the training. Moreover, 69.4% of the respondents affirmed the necessity and significance of jointly undertaking the task of analgesia and sedation in Chinese ICUs. Conclusion This study revealed that the assessment of analgesia and sedation is not standardized in the ICU in mainland China. The importance and significance of standardized training for analgesia and sedation are presented. The CASER working group thus established has a long way to go in its future work.